Variation of betaine, N, N-dimethylglycine, choline, glycerophosphorylcholine, taurine and trimethylamine-N-oxide in the plasma and urine of overweight people with type 2 diabetes over a two-year period. (May 2015) - McEntyre, Christopher J; Lever, Michael; Chambers, Stephen T; George, Peter M; Slow, Sandy; Elmslie, Jane L; Florkowski, Christopher M; Lunt, Helen; Krebs, Jeremy D
Background: Plasma betaine concentrations and urinary betaine excretions have high test-retest reliability. Abnormal betaine excretion is common in diabetes. We aimed to confirm the individuality of plasma betaine and urinary betaine excretion in an overweight population with type 2 diabetes and compare this with the individuality of other osmolytes, one-carbon metabolites and trimethylamine- N -oxide (TMAO), thus assessing their potential usefulness as disease markers. Methods: Urine and plasma were collected from overweight subjects with type 2 diabetes at four time points over a two-year period. We measured the concentrations of the osmolytes: betaine, glycerophosphorylcholine (GPC) and taurine, as well as TMAO, and the one-carbon metabolites, N, N -dimethylglycine (DMG) and free choline. Samples were measured using tandem mass spectrometry (LC-MS/MS). Results: Betaine showed a high degree of individuality (or test-retest reliability) in the plasma (index of individuality = 0.52) and urine (index of individuality = 0.45). Betaine in the plasma had positive and negative log-normal reference change values (RCVs) of 54% and −35%, respectively. The other osmolytes, taurine and GPC were more variable in the plasma of individuals compared to the urine. DMG and choline showed high individuality in the plasma and urine. TMAO was highly variable in the plasma and urine (log-normal RCVs ranging from 403% to −80% in plasma). Conclusions: Betaine is highly individual in overweight people with diabetes. Betaine, its metabolite DMG, and precursor choline showed more reliability than the osmolytes, GPC and taurine. The low reliability of TMAO suggests that a single TMAO measurement has low diagnostic value.